STUDI POTENSI DAN PROBLEMATIKA DESA TERTINGGAL DI KABUPATEN KONAWE SELATAN - Peribadi, Peribadi; Arsya, Muhammad; Samsul, Samsul; Patuju, La; P., Iwan (Fakultas Pertanian Universitas Halu Oleo, 2023)
Analysis of all types of resources from the perspective of the Village Development Index (IDM), will clearly show all potential resources as strengths and as opportunities for future development. On the other hand, various life problems are also revealed as weaknesses and challenges that can be anticipated and must even be turned into opportunities for developing disadvantaged village communities. The research aims to describe the various potentials and at the same time the various problems contained in rural areas categorized as Disadvantaged Villages in South Konawe Regency. In this context, the resource potential within the scope of the Social Resilience Index, Economic Resilience and Environmental Resilience is studied from the perspective of the Regulation of the Minister of Villages, Development of Disadvantaged Regions and Transmigration of the Republic of Indonesia Number 2 of 2016 concerning the Developing Village Index. The research uses a qualitative approach which focuses on descriptive studies and phenomenological studies. All components of South Konawe society that are deemed worthy of providing information can be used as primary data sources. Primary data was carried out using participant observation, surveys, deep interviews and Focus Group Discussions. Analysis of the Village Development Index (IDM) through a process of weighting and ranking rural resource potential. The results of the research show that there is a rural area that is classified as a Very Disadvantaged Village (Pritama Village), because it is in the value range of less than 0.4907 and the existence of an area that is in the Disadvantaged Village category because it has a value of less than 0.599. Such conditions indicate vulnerability to natural disasters, economic shocks and social conflicts, so that villages experience difficulties in managing and utilizing the potential of their social, economic and ecological resources. The portrait of rural areas referred to as underdeveloped and very underdeveloped villages depicts the worst condition of resources according to the provisions of the 2016 Minister of Village Regulation, so that it appears very problematic in developing its existence towards developing villages, developed villages and up to independent villages. The existence of underdeveloped and very underdeveloped villages appears on the one hand to have sufficient resource potential to support the development of a rural area and develop the socio-economic welfare of its people. Although on the other hand, it was not able to achieve a score according to the provisions of the 2016 Minister of Village Regulation. In this context, for example, in the education dimension, high points were achieved, but the achievement in the social capital dimension appeared to be very low.